Komunikasi Pemerintah Pusat Dan Pemerintah Daerah: Kasus Dinamika Pelaksanaan Local Lockdown Dalam Mencegah Penyebaran COVID-19 - Ardi Putra; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2021)
In implementing the local lockdown, a good communication relationship must be established between the Central Government and Regional Governments in preventing the spread of Covid-19 at the local level. (Sedarmayanti, 2018) explained that at least there are several elements in government communication, including; Communicators, Messages, Media, Communicate and Feedback. Based on the background above, the problem formulation that the writer will raise is how the communication patterns of the central government and local governments: the case of the dynamics of implementing local lockdowns in preventing the spread of COVID-19, the purpose of writing this article is to find out the communication between the central government and local governments: the case of dynamics. implementation of a local lockdown to prevent the spread of covid-19. This research uses qualitative research methods with this type of research, namely literature study data collection through documentation, books, journals, and mass media. The results of this study are: the communication between the Central Government and the Regional Government does not run harmoniously, indicated by the presence of several regions implementing local lockdowns, including the City of Tegal, the City of Tasikmalaya, and the Province of Papua.